2018
DOI: 10.1136/practneurol-2018-002001
|View full text |Cite
|
Sign up to set email alerts
|

Cataplexy

Abstract: Remarkably and almost invariably, the clinical phenomenon of cataplexy results from the loss of around 40 000 hypocretin-containing neurones in the lateral hypothalamus in the context of narcolepsy type 1. Cataplexy reflects the dysregulation of rapid-eye-movement (REM) sleep, such that REM-sleep atonia intrudes inappropriately into wakefulness as brief episodes of either focal or total paralysis of voluntary muscle. The semiology of cataplexy differs between adults and children. A defining and enigmatic aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
(26 reference statements)
0
15
0
2
Order By: Relevance
“…4 Patient with cataplexy has been known to have abnormal activity in reward brain circuit. 5 Alterations of striatal dopaminergic system in narcolepsy with cataplexy also have been reported. In functional brain study, patients with narcolepsy showed increased striatal D2 receptor binding and a positive correlation between this and the frequency of cataplexy and sleep attack.…”
Section: Discussionmentioning
confidence: 97%
“…4 Patient with cataplexy has been known to have abnormal activity in reward brain circuit. 5 Alterations of striatal dopaminergic system in narcolepsy with cataplexy also have been reported. In functional brain study, patients with narcolepsy showed increased striatal D2 receptor binding and a positive correlation between this and the frequency of cataplexy and sleep attack.…”
Section: Discussionmentioning
confidence: 97%
“…Cataplexy, presented as a sudden skeletal muscle paralysis or weakness during waking, is the most disabling symptom of sleep disorder narcolepsy (Reading, 2019). In murine models of narcolepsy, cataplexy usually occurs during the active waking status of the animal, such as running, exploring, grooming, or responding to emotion stimuli (Morawska et al, 2011;Overeem et al, 2001;Reading, 2019). The brain circuitry responsible for cataplexy is not completely clear.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly a component of the narcoleptic syndrome alongside daytime sleepiness, sleep paralysis, and vivid hallucinations at the beginning and end of sleep. 4 Cataplexy is thought to represent brief episodes of REM sleep paralysis during wakefulness and probably involves the same neural networks that generate normal muscle atonia in REM sleep. Treatment of cataplexy by tricyclic antidepressants is often successful.…”
Section: Discussionmentioning
confidence: 99%